Synthesis and Antifungal and Insecticidal Activities of Novel N-Phenylbenzamide Derivatives Bearing a Trifluoromethylpyrimidine Moiety - Xuetong Yu; Wenjun Lan; Meihang Chen; Su Xu; Xiaoxi Luo; Shuhong He; Haijiang Chen; Qiang Fei; Wenneng Wu (Journal of Chemistry)
Seventeen novel N-phenylbenzamide derivatives bearing a trifluoromethylpyrimidine moiety were synthesized via four-step reactions. Their antifungal and insecticidal properties were evaluated. Antifungal test results demonstrated that some of the synthesized compounds showed better in vitro bioactivities against Phomopsis sp., Botryosphaeria dothidea (B. dothidea), and Botrytis cinerea (B. cinerea) at 50 μg/mL than pyrimethanil. Unfortunately, the synthesized compounds revealed lower insecticidal activities against Spodoptera frugiperda (S. frugiperda) and Mythimna separata (M. separata) at 500 μg/mL than chlorantraniliprole.